Convergence of an algorithm for constructing snakes - Dzyadyk, V. K.; Kovtunets, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We investigate an algorithm for constructing snakes (extremal polynomials introduced by S. Karlin) suggested by Dzyadyk. It is proved that, in the general case, this algorithm is linearly convergent. In the case where the basis functions of the Chebyshev system belong to the class $C^2$, this algorithm is quadratically convergent.